Increase in QRS amplitudes is better than N-terminal pro-B-type natriuretic peptide to predict clinical improvement in decompensated heart failure - ERDOĞAN, OKAN (CHURCHILL LIVINGSTONE INC MEDICAL PUBLISHERS, 2014)
Background: We aimed to investigate the correlation between ECG QRS voltage changes, N-terminal pro-B-type natriuretic peptide (NT-proBNP) levels and clinical improvement in decompensated heart failure (DHF). Methods and results: DHF patients (n = 56) with a mean age of 67.5 +/- 12.6 years showed limb QRS amplitude increase and NT-proBNP level decrease with clinical improvement (p < 0.001). Significant correlation was found between percent changes (Delta%) in body weight and Delta% in QRS voltages of aVR, aVF, DII, Sigma QRSI + II and Sigma QRS (all limb-leads) (r = -0.40; r = -0.35; r = -0.32; r = -0.30; r = -0.30 respectively, p < 0.05). No correlation was found between Delta% in NT-proBNP and body weight (r = -0.23, p = 0.09). Delta% NT-proBNP was correlated with Delta% QRS voltage only in aVR (r = -0.312, p = 0.019). In ROC analysis, >= 0.5 mm increase in aVR QRS Voltage was found to predict >= 5 kg weight loss with a sensitivity of 74% and specificity of 62% (p = 0.013, AUC: 0.699). Conclusions: Increase in QRS voltages especially in aVR was found to be more sensitive than NT-proBNP to predict clinical improvement in DHF. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: ECG; QRS voltage; Heart failure; aVR; NT-proBNP; Body weight; LEAD AVR; ELECTROCARDIOGRAM; PROGNOSIS; SOCIETY; VOLTAGE; RISK